An analysis of discrepancies in consent form for laparoscopic cholecystectomy in a tertiary care hospital: “FILTER” model - Mukherjee, Ramanuj; Mohanta, Arup; Samanta, Sudipta (International Surgery Journal, 2019)
Background: Informed consent is needed to be full-proof but many discrepancies arise as it is subjected to individualization for each patient depending on their IQ, personality etc. Considering all aspect, the study aims to identify the issues and seek for potential remedies through “FILTER” model. Methods: This is a retrospective, Institution-based, observational study conducted in R.G. Kar Medical College over 3 years on 500 patients who underwent laparoscopic cholecystectomy. Results: Most of the consents (79%) were taken by consultant surgeons and rest was by junior residents. Junior residents wrote the consent form on behalf of patients in most cases (67%). 78% of the forms were signed by the patient party, 23% by patient himself and 19% by the surgeons. 67% of the total consent forms were printed and rest were hand-written. 65% of the total consent forms were signed after the patient or the patient party was informed and rest were signed without informing them. CBD injury (72%), bleeding (55%), bile leak (46%) and post-op collection (37%) were the frequency of complications encountered by the patients not informed beforehand. As the patients were informed beforehand, the need for conversion to open operation (62%), retained stone (89%), cardio-respiratory (98% and 93% respectively) complications were common. Need for an open operation, cardio-respiratory complications were most commonly informed. Bleeding (10%), CBD injury (2%) and bile leak (12%) was less informed. Conclusions: Proper and more standardized procedures and protocols should be followed for obtaining consent irrespective of the intervention required.